2004
DOI: 10.1111/j.0022-202x.2004.22411.x
|View full text |Cite
|
Sign up to set email alerts
|

Epicutaneous Application of CpG Oligodeoxynucleotides with Peptide or Protein Antigen Promotes the Generation of CTL

Abstract: Immunostimulatory oligodeoxynucleotides (ODN) are effective adjuvants in the induction of humoral and cellular immune responses when administered parenterally with antigen. The skin has recently become a target organ for the design of non-invasive vaccine technologies. Using ovalbumin (OVA) as a model antigen, we demonstrate that the application of ODN sequences to tape-stripped skin promotes the induction of potent cytotoxic T lymphocyte (CTL) responses to co-administered peptide. Induction of peptide-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
42
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…We demonstrate that biodegradable multilayers can be loaded with a model protein antigen at doses physiologically relevant to vaccination, that dried multilayers release the embedded protein in a monomeric, unaggregated form on rehydration and erosion of the films, and that model patch substrates coated with multilayers and applied to tape-stripped skin (a simple procedure often used to permeabilize the outer layers of the stratum corneum in transcutaneous vaccination studies [34][35][36] ) rehydrate and dissolve in situ, releasing protein into the epidermis. Using a transgenic mouse model where epidermal antigen presenting cells (Langerhans cells) express green fluorescent protein (GFP)-tagged Major Histocompatibility Complex molecules, we demonstrate that protein antigen released from multilayer patches is acquired by these immune cells in the skin within hours of application of the film.…”
mentioning
confidence: 98%
“…We demonstrate that biodegradable multilayers can be loaded with a model protein antigen at doses physiologically relevant to vaccination, that dried multilayers release the embedded protein in a monomeric, unaggregated form on rehydration and erosion of the films, and that model patch substrates coated with multilayers and applied to tape-stripped skin (a simple procedure often used to permeabilize the outer layers of the stratum corneum in transcutaneous vaccination studies [34][35][36] ) rehydrate and dissolve in situ, releasing protein into the epidermis. Using a transgenic mouse model where epidermal antigen presenting cells (Langerhans cells) express green fluorescent protein (GFP)-tagged Major Histocompatibility Complex molecules, we demonstrate that protein antigen released from multilayer patches is acquired by these immune cells in the skin within hours of application of the film.…”
mentioning
confidence: 98%
“…Based primarily on in vitro studies, it is envisaged that LCs undergo a process of maturation coordinate with migration, where they upregulate MHC, costimulatory, and adhesion molecules, and act as potent stimulators of naive CD4 and CD8 T cells when they arrive in the lymph node (3)(4)(5). Indeed, epicutaneous immunization strategies, which are presumed to involve LC, are effective at inducing functional CTL (6,7) and have led to clinical trials with positive preliminary findings for influenza and travelers' diarrhea (www.iomai.com) (8,9).…”
mentioning
confidence: 99%
“…Two recent reports showed that epicutaneous immunization with an MHC-class I-restricted peptide or with ovalbumin protein onto tape-stripped skin induces cytotoxic T cell activity in the draining lymph node which can be further increased by coadministration of cholera toxin (16,17). Others reported that these responses can also be boosted with Toll-like receptor ligands, such as oligonucleotides and imiquimod (18,19). Thus, epicutaneous immunization elicits T cell responses in the draining lymph nodes, but inflammation in the skin is necessary for an optimal response.…”
mentioning
confidence: 99%